Social Responsibility - Muenstermann, Ingrid (IntechOpen, 2018)
With globalisation on the rise and capitalism expanding, social responsibility, corporate as well as individual social responsibility, plays an important part to save the natural environment and improve the lives of citizens. But how responsibly do corporations and ordinary citizens act in order to meet the demands of our fast-changing world? Authors from different universities contribute their knowledge on this open-access platform to be shared at a global level. This book starts off by contemplating whether the concept of world society could be an ice-breaker for a global shift in sociology (Wittmann); it critically assesses social responsibility of Spanish university students (Ramos), discusses professional social responsibility in engineering (Bielefeldt), looks at conflicts in Kenya's mining industry (Abuya) and evaluates the public healthcare system in Italy (Comite) and the corporate and consumer social responsibility in the Italian food industry (Boccia & Covino). The book also includes guidelines for managers who want to enter the corporate world (Gorondutse & Hilman) and ends with a chapter examining Chinese consumers' attitudes towards counterfeit goods (Kozar & Huang). The collective contributions of these experts provide updates regarding ongoing research and developments in relation to the urgent need for improved social responsibility.